“JEDES HERZ…”: TERROR AND HORROR IN DIE FETTEN JAHRE SIND VORBEI (Revue D’études Interculturelles De L’image, 2014)
Hans Weingartner’s Die Fetten Jahre Sind Vorbei, also known by its American title The Edukators, explores the relationship of a young anti-capitalist activist, Jan, with his own friends, the bourgeousie he opposes, and himself. Jan and his friends engage in some relatively benign but disruptive “terrorist” acts. Though the film cannot be said to belong to the horror genre, Die Fetten Jahre Sind Vorbei nonetheless employs horror elements and tropes to expose the intrinsically subjective definition of terrorism, and to explore terrorism’s relationship with the “other.”